Beyond meaning: hope and secondary trauma in Israeli therapists after the October 7th massacre - George-Levi, Sivan; Faverman, Lir; Galin-Lonchich, Yael; Ben-Gal Dahan, Anat; Frei-Landau, Rivi (Frontiers in Psychology, 2025)
The massacre on October 7th, 2023 in southern Israel had a profound impact on mental health therapists in the region. Such collective trauma can lead to heightened stress and secondary trauma among therapists. Identifying resilience and risk factors is, therefore, essential for mitigating these effects. This preliminary study involved 60 therapists (75% women; M = 48.3 years, SD = 10.7) from the Sderot Resilience Center, located near the Gaza border, who completed questionnaires about demographic, professional, and war-related factors, as well as secondary trauma symptoms, finding meaning in work, sense of hope, and stress levels during the war, 1 year after the attack. Loss of a loved one during the war was associated with higher stress levels. Secondary trauma symptoms were linked with increased stress, and higher levels of hope were associated with reduced stress. Moderation models indicated that finding meaning in work was associated with lower stress only when secondary trauma symptoms were low or moderate, but not when they were high. Higher hope levels were linked to reduced stress regardless of secondary trauma severity. Although preliminary and cross-sectional, these findings suggest that whereas finding meaning in work may motivate therapists, it may not fully protect them against stress during extreme trauma. Hope, however, appears to offer a stronger protective buffer. Interventions to mitigate risk factors, reduce secondary trauma, and foster hopeful thinking are essential.